2008
DOI: 10.1016/j.jpainsymman.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Discomfort as the Fifth Vital Sign Using an Electronic Medical Recording System: A Feasibility Study

Abstract: Late referral to a specialized palliative care service hinders quality symptomatic management. The aim of this article is to describe the feasibility and clinical usefulness of screening for patient discomfort as the fifth vital sign using an electronic medical recording system to identify patients with undertreated physical symptoms. For the electronic medical recording system, all admitted patients received routine nurse assessment of discomfort (defined as any physical symptom) at every vital signs check us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…An additional advantage of this type of computerized system could be for specialized teams – such as pain specialists – to screen records of inpatients so that they could visit and review those patients with documented pain not otherwise referred to them (similarly to what has been proposed for the screening of discomfort of cancer patients by palliative care teams [ 35 ]). This is also an example of the ‘new uses’ generated by the introduction of electronic systems in place of paper-based ones and how their clinical utility extends to new aspects of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage of this type of computerized system could be for specialized teams – such as pain specialists – to screen records of inpatients so that they could visit and review those patients with documented pain not otherwise referred to them (similarly to what has been proposed for the screening of discomfort of cancer patients by palliative care teams [ 35 ]). This is also an example of the ‘new uses’ generated by the introduction of electronic systems in place of paper-based ones and how their clinical utility extends to new aspects of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…To help standardize symptom assessment into routine clinical care, several large oncology settings have invested in electronic systems to capture patientreported symptom data. 1 Electronic symptom assessment has been shown to be feasible and efficient at helping to standardize screening, inform symptom management, and monitor adverse events and quality [1][2][3][4] ; however, it also represents a major investment in time and resources by the oncology system. Several randomized trials using electronic symptom reporting have suggested that routinely providing oncology providers with patient-reported symptom outcomes is beneficial, though the evidence is nuanced, with limitations to specific symptoms, particular tools or interventions, or nonsignificant results.…”
Section: Introductionmentioning
confidence: 99%
“…Most common action taken by GP was to start an electronic anticipatory care plan. Morita et al, 22 Schizuoka, Japan Feasibility study of 629 male and female oncology patients screened for discomfort in a Japanese 700 bed cancer hospital Alert: CDS automatically screened pain scores; produce trigger for PC team Identified undertreated symptoms. Feasible to identify patients with considerable physical discomfort using EHR; no patient burden; minimal nursing burden.…”
Section: Resultsmentioning
confidence: 99%
“… 45 Other suggestions included adding additional diagnosis codes to the alert system to identify specific symptoms in patients who are not yet in need of PC, but can benefit from a change in treatment course or to alleviate discomfort. 19 , 22 …”
Section: Discussionmentioning
confidence: 99%